2022
DOI: 10.1101/2022.11.07.22282037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heat Exposure Among Adult Women in Rural Tamil Nadu, India

Abstract: Exposure to heat is associated with a substantial burden of disease and is an emerging issue in the context of climate change. Heat exposure is of particular concern in India, one of the world's hotter countries and soon to be its most populous, where a large fraction of the population works outdoors, lives in dwellings that are thermally inefficient, and is unable to access cooling technologies. Despite these concerns, relatively little is known about personal heat exposure in India, particularly in rural are… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…14,16,[28][29][30][31] Of the limited studies on personal temperature measurements in LMICs, most were conducted in warm, rural regions of India (generally >18°C in the cool season) and involved relatively short-term (24-hour) assessment in limited sample sizes, with only two studies having repeated measurements across seasons. [18][19][20] These studies found a moderate-to-strong agreement between personal or household temperatures and outdoor temperature in general, but a somewhat weaker association in the cool season. [18][19][20] Compared to previous personal measurement studies, in the CKB-Air we captured 6-10 times greater amount of data (in person-hours) across a broader outdoor temperature range (mean daily temperature range: -3.9°C to 42.6°C) and across the personal, household, and outdoor environments.…”
Section: Relationships Between Temperatures Across Microenvironmentsmentioning
confidence: 79%
“…14,16,[28][29][30][31] Of the limited studies on personal temperature measurements in LMICs, most were conducted in warm, rural regions of India (generally >18°C in the cool season) and involved relatively short-term (24-hour) assessment in limited sample sizes, with only two studies having repeated measurements across seasons. [18][19][20] These studies found a moderate-to-strong agreement between personal or household temperatures and outdoor temperature in general, but a somewhat weaker association in the cool season. [18][19][20] Compared to previous personal measurement studies, in the CKB-Air we captured 6-10 times greater amount of data (in person-hours) across a broader outdoor temperature range (mean daily temperature range: -3.9°C to 42.6°C) and across the personal, household, and outdoor environments.…”
Section: Relationships Between Temperatures Across Microenvironmentsmentioning
confidence: 79%
“…[14,16,[28][29][30][31] Of the limited studies on personal temperature measurements in LMICs, most were conducted in warm, rural regions of India (generally >18°C in the cool season) and involved relatively short-term (24-hour) assessment in limited sample sizes, with only two studies having repeated measurements across seasons. [18][19][20] These studies found a moderate-to-strong agreement between personal or household temperatures and outdoor temperature in general, but a somewhat weaker association in the cool season. [18][19][20] Compared to previous personal measurement studies, in the CKB-Air we captured 6-10 times greater amount of data (in person-hours) across a broader outdoor temperature range (mean daily temperature range: -3.9°C to 42.6°C) and across the personal, household, and outdoor environments.…”
Section: Relationships Between Temperatures Across Microenvironmentsmentioning
confidence: 99%
“…[18][19][20] These studies found a moderate-to-strong agreement between personal or household temperatures and outdoor temperature in general, but a somewhat weaker association in the cool season. [18][19][20] Compared to previous personal measurement studies, in the CKB-Air we captured 6-10 times greater amount of data (in person-hours) across a broader outdoor temperature range (mean daily temperature range: -3.9°C to 42.6°C) and across the personal, household, and outdoor environments. In summer, we found a strong agreement between personal and household or outdoor temperatures.…”
Section: Relationships Between Temperatures Across Microenvironmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cookstove intervention studies often monitor temperature exposures while also collecting biospecimens and cardiorespiratory data. 8 However, studies employing the technologies used by Meade et al. to evaluate physiological temperature (e.g., ingestible monitors, rectal thermocouple-based monitors, skin-based thermistors) are rare and may not be feasible in the field from the perspective of either acceptability or practicality.…”
mentioning
confidence: 99%